Relationship work among young adult couples: Romantic, social, and physiological considerations. Issue 2 (3rd June 2019) - Jensen, Jakob; Fish, Matthew; Dinkins, Quianna; Rappleyea, Damon; Didericksen, Katharine W.
Abstract: We examined romantic, social, and physiological variables associated with partners discussing romantic challenges together and with friends, a process known as relationship work (RW). Actor‐partner interdependence models examining 71 heterosexual, young adult couples and their friends suggested social network approval, friendship quality, and partners' perspective taking were each associated with partners' RW patterns. Skin conductance activity readings revealed males universally experienced greater physiological arousal when discussing romantic problems than females. Unexpectedly, both males and females experienced greater skin conductance activity when discussing romantic challenges with friends than with partners. Males were more likely to discuss romantic challenges with friends when their female partners experienced greater baseline skin conductance activity. Findings inform researchers regarding links between romantic, social, and physiological functioning.